PENERAPAN PEMBELAJARAN FISIKA MENGGUNAKAN MODEL DISCOVERY LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 2 KOTAMOBAGU - Franklien Lumettu; Djeli Alvi Tulandi; Jeane Rende (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2020)
Physics learning is currently still dominated by teacher centered that the principle of learning interaction is oriented to the transfer of knowledge. The research do to determine the application of discovery learning models in improving student learning outcomes. This research was conducted at SMP Negeri 2 Kotamobagu for the subject of light and optical devices. The research method used was the classroom action research model of Jhon Elliot. Data collection was performed on 20 students of class VIII. Data analysis uses percentages based on mastery learning references. The results obtained showed that the application of discovery learning models can improve student learning outcomes and this is seen from the average value of the class. At meeting I the average value was 62, at meeting II 71.25 and at meeting III reached 80.25. The percentage of mastery learning also shows the same thing where at the first meeting the value of completeness percentage 65%, at meeting II 85% and at meeting III reached 100%. The results of this study concluded that the discovery learning model was suitable for use in learning physics in class VIII junior high school on the topic of light and optical devices